Internal auditing practices and internal control system - Fadzil, Faudziah Hanim; Haron, Hasnah; Jantan, Muhamad (Emerald Group Publishing Limited, 2005)
Purpose– Two main objectives and they are: to determine whether the internal audit department of the companies listed in the Bursa Malaysia complies with the Standards for the Professional Practice of Internal Auditors IIA (2000); and, to determine whether compliance to SPPIA will affect the quality of the internal control system of the company.Design/methodology/approach– Two sets of questionnaires were used in the study. Internal auditing practices was measured by the items listed in the SPPIA and the internal control was measured by means of the statement on internal control: guidance for directors of public listed companies.The population used in this study was all the companies listed in the Bursa Malaysia in 2001. This study used both descriptive and inferential analyses.Findings– It was found that management of internal audit department, professional proficiency, objectivity and review significantly influence the monitoring aspect of the internal control system. Scope of work and performance of audit work significantly influences the information and communication aspect of the internal control system while performance of audit work, professional proficiency and objectivity significantly influence the control environment aspect of the internal control system. The study also shows that management of internal audit department, performance of audit work, audit program and audit reporting significantly influences the risk assessment aspect of the internal control system. Lastly, performance of audit work and audit reporting significantly influences the control activities aspect of the internal control system.Research limitations/implications– The research has contributed to the agency theory with respect to the bonding costs that management has to pay to the internal auditors for the best interest of the principals of the companies. Another important implication pertains to the extent of the internal auditing practices among internal auditors in Malaysian public listed companies. Research has also shown that the compliance with internal auditing practices partially influence certain aspects of the quality of the internal control system.Originality/value– This is the first empirical study that has linked the compliance of the internal auditing function to the SPPIA and its effect on the internal control system.